GREEN TECHNOLOGIES: THE ROLE OF GREEN PATENTS FOR INNOVATION, PRESERVATION AND SUSTAINABLE DEVELOPMENT - Salgado, Eduardo Gomes (2023)
Objective: Demonstrate how the Green Patents Program contributes to the encouragement and development of technologies that benefit the environment. Theoretical framework: In the current scenario of environmental degradation, green technologies are linked to the need for technological and economic development in order to contribute to the environment and sustainable development. In fostering research and development of environmentally sustainable products, the patent system acts in favor of innovation and technology aimed at solving environmental issues around the world. In Brazil, the Green Patents Program of the National Institute of Intellectual Property (INPI) seeks to speed up the examination of patent applications related to technologies aimed at the environment. Method: Systematic review of the literature with a qualitative approach to the data. Results and conclusion: Green patents stimulate the creation and development of technologies capable of reducing and/or controlling environmental impacts by making use of the industrial property system by accelerating procedures involving the granting of patents, favoring both socioeconomic growth and development sustainable as today's society and future generations. Research implications: The academic, managerial and social contribution of knowing green patents lies in their relevance in innovation, preservation and sustainable development that reach the environment, public and private institutions and society. Originality/value: Contribute to the enrichment and dissemination of information on actions that encourage the use of green patents.